USING FINITE ELEMENT METHOD AND FATIGUE ASSESSMENT OF SINGLE - SCREW FISH OIL EXTRUDER - Tarek FOUDA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Modelling by Finite Element Method (FEM) and fatigue assessment of the single-screw of a press for obtaining fish oil through Solidworks software. Fish oil is a dietary supplement resulting from the tissues of fatty fish, such as salmon, mackerel, herring, and other different types of fish. It is rich in omega-3 fatty acids, and this oil is extracted using an extrusion machine. The objective of this study is to design and analyze extruder parts by finite element analysis at the Department of Agricultural Engineering - Faculty of Agriculture, Egypt. The functional parts of the machine include a feeder, nozzle (barrel), filter mesh, pressure chambers 1 and 2, screw axis, and finally a waste outlet. As for finite element analysis, 9 indicators were studied such as Von Mises, yield strength, INT (stress intensity), TRI (triaxle stress), static displacements, RFRES (resultant reaction), ESTRN (equivalent strain), SEDENS (strain energy density, and ENERGY (total strain energy), and the results for screw axle were (3.12e+07 N/m2, 1.72e+08 N/m2, 3.60e+07 N/m2, 3.71e+07 N/m2, 3.17e-02 mm, 1.91e+02N, 1.08e-04,1.41e+03 N.m/m3, 4.41e-15 N.m) when applied 100 N as a torque load, this axle can press 5 times the added weight of fish waste. Also, for screw axis, the results of fatigue indices such as load factor and biaxiality were (7.72e+08, and 9.34e-01) respectively.